Effects of reclaimed water irrigation and nitrogen fertilization on the chemical properties and microbial community of soil - Wei GUO; Mathias N Andersen; Xue-bin QI; Ping LI; Zhong-yang LI; Xiang-yang FAN; Yuan ZHOU (Journal of Integrative Agriculture)
The ecological effect of reclaimed water irrigation and fertilizer application on the soil environment is receiving more attention. Soil microbial activity and nitrogen (N) levels are important indicators of the effect of reclaimed water irrigation on environment. This study evaluated soil physicochemical properties and microbial community structure in soils irrigated with reclaimed water and receiving varied amounts of N fertilizer. The results indicated that the reclaimed water irrigation increased soil electrical conductivity (EC) and soil water content (SWC). The N treatment has highly significant effect on the ACE, Chao, Shannon (H) and Coverage indices. Based on a 16S ribosomal RNA (16S rRNA) sequence analysis, the Proteobacteria, Gemmatimonadetes and Bacteroidetes were more abundant in soil irrigated with reclaimed water than in soil irrigated with clean water. Stronger clustering of microbial communities using either clean or reclaimed water for irrigation indicated that the type of irrigation water may have a greater influence on the structure of soil microbial community than N fertilizer treatment. Based on a canonical correspondence analysis (CCA) between the species of soil microbes and the chemical properties of the soil, which indicated that nitrate N (NO3−-N) and total phosphorus (TP) had significant impact on abundance of Verrucomicrobia and Gemmatimonadetes, meanwhile the pH and organic matter (OM) had impact on abundance of Firmicutes and Actinobacteria significantly. It was beneficial to the improvement of soil bacterial activity and fertility under 120 mg kg−1N with reclaimed water irrigation.